Unofficial policy: access to housing, housing information and social services among homeless drug users in Hartford, Connecticut. - Dickson-Gomez, Julia; Convey, Mark; Hilario, Helena; Corbett, A Michelle; Weeks, Margaret (Substance abuse treatment, prevention, and policy, 2007)
Much research has shown that the homeless have higher rates of substance abuse problems than housed populations and that substance abuse increases individuals' vulnerability to homelessness. However, the effects of housing policies on drug users' access to housing have been understudied to date. This paper will look at the "unofficial" housing policies that affect drug users' access to housing.
Keywords: Adult; Community Health Services; Connecticut; Drug Users; Female; Health Services Accessibility; Homeless Persons; Housing; Humans; Information Dissemination; Interviews as Topic; Longitudinal Studies; Male; Middle Aged; Public Policy; Social Support; Social Work